The evaluation of human resources management processes changes: theoretical and practical aspects - Juodeikaitė, Monika; Fominienė, Asta (Information & Media, 2016)
Changes in human resources (HR) management theories show that HR management is very sensitive to environmental factors. Modern organisations are constantly facing changes and their influence is growing rapidly. The levels of influence are growing too. Organisational management is affected not only by factors at country level, but also at international level. Globalisation, European Union and others communities have a significant influence too. In the recent times, the HR management processes are becoming the subject of scientific research and the main problem is the organisations’ collision with HR management changes that necessitates the re-evaluation of HR management processes, taking into account the factors affecting it, in order to align the company’s owner and employee objectives and ensuring the efficient creation of added value. In theoretical level, the article highlights environmental factors in HR management concepts and the HR management process structure within the context and functions, identifies the HR management process place in the whole company’s processes system and analyses strategic HR management models. HR management processes model is created based on theoretical analysis. The practical problem is solved by adapting theoretical model and using a two-part research methodology, which includes a questionnaire survey of employees and expert interviews. After the research, the theoretical model was improved and shows the relations and actions how to evaluate the internal and external factors that affect organisation’s human resources management and how the changes of HR processes correlates with results.
Keywords: ...